Solid state battery
By using a negative electrode active material with a lithium-to-metal molar ratio of 2.0 or more, particularly with tungsten, in combination with a garnet-type solid electrolyte, the reaction between these components is suppressed, improving the utilization rate and performance of solid batteries.
Patent Information
- Application Number
- JP2023503790
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-01
- Filing Date
- 2022-02-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-02-25
AI Technical Summary
Traditional solid batteries using garnet-type solid electrolytes react excessively with negative electrode active materials during sintering, leading to a decrease in the utilization rate of these materials.
Incorporating a specific negative electrode active material with a lithium-to-metal molar ratio (Li/m) of 2.0 or more, particularly with tungsten (W), combined with a garnet-type solid electrolyte, to suppress the reaction and maintain the integrity of the negative electrode layer.
The combination effectively reduces the reaction between the garnet-type solid electrolytes and negative electrode active materials, thereby enhancing the utilization rate and maintaining the performance of the solid battery.
Smart Images

Figure 0007622816000010 
Figure 0007622816000011 
Figure 0007622816000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid-state battery. [Background technology]
[0002] In recent years, the demand for batteries (especially secondary batteries) as power sources for portable electronic devices such as mobile phones and portable personal computers has increased significantly. In secondary batteries used for such purposes, non-aqueous electrolytes (electrolytic solutions) such as organic solvents have traditionally been used as a medium for transferring ions. In such non-aqueous electrolyte secondary batteries, attempts have been made to improve battery characteristics such as average discharge potential and charge / discharge hysteresis by using Li4WO5 as the negative electrode active material (for example, Patent Document 1).
[0003] However, there is a risk of electrolyte leakage in the battery with the above configuration, and the organic solvents used in the electrolyte are flammable. For this reason, it has been proposed to use a solid electrolyte instead of the electrolyte. Development of a sintered solid secondary battery (so-called "solid-state battery") that uses a solid electrolyte as the electrolyte and has other components that are also solid is underway.
[0004] The solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer laminated between the positive electrode layer and the negative electrode layer. In such a solid-state battery, it has been reported that a solid electrolyte having a garnet structure (e.g., LLZ) has a relatively high ionic conductivity and a wide potential window (Non-Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-201223 A [Non-patent literature]
[0006] [Non-Patent Document 1] R. Murugan et al., Angew. Chem. Int. Ed., 2007, 46, 7778-7781 Summary of the Invention [Problem to be solved by the invention]
[0007] The inventors of the present invention have found that in the above-mentioned conventional solid-state batteries, the reactivity between the garnet-type solid electrolyte and the electrode active material is very high, and sufficient battery performance cannot be obtained.
[0008] Specifically, when a garnet-type solid electrolyte is contained in the negative electrode layer together with a negative electrode active material in a solid-state battery, the garnet-type solid electrolyte reacts with the negative electrode active material during sintering, resulting in a decrease in the utilization rate of the negative electrode active material. For this reason, a negative electrode active material that has a sufficiently low reactivity with the garnet-type solid electrolyte during sintering has been desired.
[0009] An object of the present invention is to provide a solid-state battery capable of more sufficiently suppressing a decrease in the utilization rate of the negative electrode active material even when a garnet-type solid electrolyte is contained in the negative electrode layer. [Means for solving the problem]
[0010] The present invention relates to a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; The negative electrode layer relates to a solid-state battery comprising a negative electrode active material that contains Li (lithium), M [M is one or more elements selected from the group consisting of W (tungsten), Mo (molybdenum), Ta (tantalum) and Zr (zirconium)], and O (oxygen), and in which the molar ratio (Li / M) of the Li content to the M content is greater than 2.0, and a garnet-type solid electrolyte.
[0011] The present invention is based on the discovery that a specific negative electrode active material is an electrode material that can withstand co-sintering with a garnet-type solid electrolyte. More specifically, the inventors of the present invention have found that by combining a garnet-type solid electrolyte with a specific negative electrode active material, the reaction between them can be sufficiently suppressed. Effect of the Invention
[0012] The solid-state battery according to the present invention can more sufficiently suppress the reaction between the garnet-type solid electrolyte and the negative electrode active material in the negative electrode layer. In the solid-state battery of the present invention, even though the negative electrode layer contains a garnet-type solid electrolyte, the decrease in the utilization rate of the negative electrode active material can be more sufficiently suppressed. [Brief description of the drawings]
[0013] [Figure 1] 1 shows X-ray diffraction patterns (i.e., XRD patterns) measured in the examples. [Figure 2A] 4 shows charge / discharge curves of the solid-state battery produced in Example 4. [Figure 2B] 4 shows charge / discharge curves of the solid-state battery produced in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [Solid battery] The present invention provides a solid-state battery. In the present specification, the term "solid-state battery" refers in a broad sense to a battery whose components (particularly the electrolyte layer) are made of solids, and in a narrow sense to an "all-solid-state battery" whose components (particularly all components) are made of solids. In the present specification, the term "solid-state battery" includes so-called "secondary batteries" that can be repeatedly charged and discharged, and "primary batteries" that can only be discharged. The "solid-state battery" is preferably a "secondary battery." The term "secondary battery" is not excessively limited by its name, and may also include electrochemical devices such as "electricity storage devices."
[0015] The solid-state battery of the present invention includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, and usually has a laminated structure in which a solid electrolyte layer is laminated between the positive electrode layer and the negative electrode layer. The positive electrode layer and the negative electrode layer may each be laminated in two or more layers as long as a solid electrolyte layer is provided between them. The solid electrolyte layer is in contact with the positive electrode layer and the negative electrode layer and is sandwiched between them. The positive electrode layer and the solid electrolyte layer may be sintered together as a sintered body, and / or the negative electrode layer and the solid electrolyte layer may be sintered together as a sintered body. The term "sintered together as a sintered body" means that two or more adjacent or contacting members (particularly layers) are joined by sintering. Here, the two or more members (particularly layers) may be sintered together as a sintered body. The solid-state battery of the present invention may be referred to as a "sintered solid-state battery" or a "co-sintered solid-state battery" in the sense that the positive electrode layer and the solid electrolyte layer are sintered together as sintered bodies, and the negative electrode layer and the solid electrolyte layer are sintered together as sintered bodies.
[0016] (Negative electrode layer) The negative electrode layer is a layer capable of absorbing and releasing metal ions, and is preferably a layer capable of absorbing and releasing lithium ions. The negative electrode layer includes a negative electrode active material and a solid electrolyte.
[0017] The negative electrode active material contains Li (lithium), M [M is one or more elements selected from the group consisting of W (tungsten), Mo (molybdenum), Ta (tantalum) and Zr (zirconium)] and O (oxygen), and has a molar ratio (Li / M) of the Li content to the M content of greater than 2.0. When the negative electrode active material does not contain M, or when Li / M in the negative electrode active material is 2.0 or less, the solid electrolyte reacts with the negative electrode active material during sintering, resulting in a decrease in the utilization rate of the negative electrode active material.
[0018] The negative electrode active material preferably contains W as the above-mentioned M from the viewpoint of suppressing the reaction between the solid electrolyte and the negative electrode active material. The charge / discharge capacity of this negative electrode active material is expressed by the redox of W. The inclusion of W as M means that, for example, in the general formula (N) described later, β with respect to W (i.e., a number corresponding to β with respect to W) satisfies 0<β<1.5, preferably 0.4≦β≦1.2, more preferably 0.6≦β≦1.02, and further preferably 0.7≦β≦1.02. It is more preferable that M is W from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material.
[0019] The negative electrode active material preferably has a chemical composition represented by general formula (N) from the viewpoint of suppressing the reaction between the solid electrolyte and the negative electrode active material.
[0020] [ka]
[0021] In formula (N), M is the same as M described above. From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, M preferably contains W, more preferably contains W. When M contains W (tungsten), M may contain W (tungsten) in combination with one or more elements Mx selected from the group consisting of Mo (molybdenum), Ta (tantalum) and Zr (zirconium). M' is one or more elements selected from the group consisting of Na (sodium), K (potassium), Ca (calcium), Ti (titanium), V (vanadium), Sn (tin), Nb (niobium), Zn (zinc), Mn (manganese), Mg (magnesium), Al (aluminum), and Ga (gallium). M' may also be a metal element that can replace a portion of the Li element.
[0022] α satisfies 2<α<10, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, preferably satisfies 3≦α≦8, more preferably 3≦α≦5.5, even more preferably 3.9≦α≦5.5, particularly preferably 3.9≦α≦5.0, and most preferably 3.9≦α≦4.5. β satisfies 0<β<1.5, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that 0.4≦β≦1.2, more preferably 0.6≦β≦1.05, even more preferably 0.7≦β≦1.02, particularly preferably 0.9≦β≦1.03, and most preferably 1. When M contains two or more elements, the total number of β for each element (i.e., the number corresponding to β for each element) may be within the above-mentioned β range. When M contains two or more elements, each of the β for each element (i.e., the number corresponding to β for each element) may be independently 0.01 or more and 1.2 or less, particularly 0.05 or more and 1.05 or less. In particular, when M contains a combination of W (tungsten) and one or more elements Mx selected from the group consisting of Mo (molybdenum), Ta (tantalum), and Zr (zirconium), β for W (hereinafter, β) is 0.01 or more and 1.2 or less, and particularly 0.05 or more and 1.05 or less. W ) and β with respect to Mx (hereafter, β Mx From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that the above-mentioned range is as follows: ·β W is between 0.5 and 1.1, in particular between 0.7 and 1.0; ·β Mx is 0.05 or more and 0.4 or less, particularly 0.1 or more and 0.3 or less; when Mx contains two or more elements, β Mx (i.e., β for each element Mx The total number of the above β Mx It is sufficient if the range is within the range.
[0023] γ satisfies 0≦γ<3, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, preferably satisfies 0≦γ≦2, more preferably 0≦γ≦1, further preferably 0≦γ≦0.4, and particularly preferably is 0. When M′ contains two or more elements, it is sufficient that the total number of γ for each element (i.e., the number corresponding to γ for each element) is within the above range of γ. ω satisfies 4<ω<9, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, preferably satisfies 4<ω≦7 (particularly 5, 6 or 7), more preferably 4.5≦ω≦6.5 (particularly 5 or 6), even more preferably 4.5≦ω≦5.5, and even more preferably 5.
[0024] α / β is a value corresponding to the molar ratio (Li / M) of the Li content to the M content described above, and is greater than 2. From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, α / β is preferably 2<α / β≦7, more preferably 3≦α / β≦6.5, even more preferably 3.8≦α / β≦6.5, particularly preferably 3.8≦α / β≦5.5, and most preferably 3.8≦α / β≦5.0.
[0025] The chemical composition of the negative electrode active material may be an average chemical composition. The average chemical composition of the negative electrode active material may be directly measured by breaking the solid-state battery and using TEM-EELS (electron energy loss spectroscopy) or Auger electron spectroscopy. In the negative electrode layer, the average chemical composition of the negative electrode active material and the average chemical composition of the solid electrolyte described below can be measured separately based on their compositions in the above composition analysis (an element contained only in the solid electrolyte can be detected, and a portion where the element is not detected can be regarded as the negative electrode active material. For example, when the solid electrolyte contains La and the electrode active material does not contain La, a portion where La is not detected is regarded as the negative electrode active material, and a portion where La is detected is regarded as the solid electrolyte).
[0026] Specific examples of the negative electrode active material represented by the general formula (N) include Li4WO5, Li 3.8 W 1.03 O5, Li6WO6, Li4(W 0.8 Mo 0.2)O5, Li 4.4 (W 0.8 Zr 0.2 )O5, Li 4.1 (W 0.9 Ta 0.1 )O5, Li 4.23 W 0.96 O5, and Li 3.84 Mg 0.2 W 0.96 Examples include O5.
[0027] From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, the negative electrode active material preferably has one or more crystal structures selected from the group consisting of a low-temperature phase Li4WO5 type crystal structure, a high-temperature phase Li4WO5 type crystal structure, and a Li6WO6 type crystal structure, more preferably has a low-temperature phase Li4WO5 type crystal structure or a high-temperature phase Li4WO5 type crystal structure, and even more preferably has a high-temperature phase Li4WO5 type crystal structure.
[0028] In the present invention, the negative electrode active material has a low-temperature phase Li4WO5 type structure means that the negative electrode active material has a crystal structure that can be assigned to ICDD Card No. 01-074-6445. For example, the negative electrode active material has a low-temperature phase Li4WO5 type structure means that the negative electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called low-temperature phase Li4WO5 type crystal structure at a predetermined incidence angle in X-ray diffraction. The low-temperature phase Li4WO5 type structure is the so-called α-Li4WO5 type structure.
[0029] In the present invention, the negative electrode active material having a high-temperature phase Li4WO5 type structure means that the negative electrode active material has a crystal structure that can be assigned to any of ICDD Card Nos. 01-074-6193, 00-021-0530, or 04-010-6772. For example, the negative electrode active material having a high-temperature phase Li4WO5 type structure means that the negative electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called high-temperature phase Li4WO5 type crystal structure at a predetermined incidence angle in X-ray diffraction. The high-temperature phase Li4WO5 type structure includes the so-called β-Li4WO5 type structure and structures similar thereto. Examples of the similar structures include, for example, crystal structures that can be assigned to any of ICDD Card Nos. 00-021-0530 or 04-010-6772 among the above-mentioned crystal structures.
[0030] In the present invention, the negative electrode active material having a Li6WO6 type structure means that the negative electrode active material has a crystal structure that can be assigned to ICDD Card No. 01-073-6224. For example, the negative electrode active material having a Li6WO6 type structure means that the negative electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called Li6WO6 type crystal structure at a predetermined incident angle in X-ray diffraction.
[0031] The lattice constant of the negative electrode active material in the present invention changes due to charging and discharging (Li insertion and removal). Therefore, it is not necessary for the lattice constant to be strictly equal to that of the ICDD card, but it is sufficient for the lattice constant to be close to that of the ICDD card. In the present invention, closeness means a numerical range within ±10% of the lattice constant of the ICDD card.
[0032] From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that the negative electrode active material has a single-phase structure of a high-temperature phase Li4WO5 type crystal structure. The single-phase structure of a high-temperature phase Li4WO5 type crystal structure is a structure in which the intensity of the strongest peak specific to each crystal structure in X-ray diffraction (XRD using CuKα rays) is I H is a crystal structure in which the intensity of the strongest peak (peak at an incident angle of about 2θ = 18°) specific to the high-temperature phase Li4WO5-type crystal structure is 80% or more of the sum of the intensities of all the strongest peaks. For example, a single-phase structure of the high-temperature phase Li4WO5-type crystal structure is a crystal structure in which the intensity of the strongest peak (peak at an incident angle of about 2θ = 18°) specific to the high-temperature phase Li4WO5-type crystal structure is 80% or more of the sum of the intensities of all the strongest peaks. H and the intensity I of the strongest peak specific to the low-temperature phase Li4WO5-type crystal structure (e.g., the peak near the incident angle 2θ = 44°). L But, I H / (I H +I L ) ≧ 0.80. H and I L I H / (I H +I L )<0.80 is considered to be mixed phase.
[0033] The negative electrode active material may have the above-mentioned chemical composition and crystal structure in the solid-state battery after the negative electrode layer is sintered together with the positive electrode layer and the solid electrolyte layer.
[0034] The negative electrode active material can be produced, for example, by the following method. First, raw material compounds containing predetermined metal atoms are weighed so as to have a predetermined chemical composition, and water is added and mixed to obtain a slurry. The slurry is dried, calcined at 700°C to 1000°C for 4 hours to 24 hours, and pulverized to obtain the negative electrode active material.
[0035] The average particle size of the negative electrode active material is not particularly limited and may be, for example, 0.01 μm or more and 20 μm or less, and preferably 0.1 μm or more and 5 μm or less.
[0036] The average particle size (arithmetic mean) of the negative electrode active material can be determined, for example, by randomly selecting 10 to 100 particles from an SEM image and simply averaging their particle sizes.
[0037] The particle diameter is the diameter of a spherical particle when the particle is assumed to be a perfect sphere. Such a particle diameter can be obtained, for example, by cutting out a cross section of a solid-state battery, taking a cross-sectional SEM image using a SEM, calculating the cross-sectional area S of the particle using image analysis software (for example, "A-zo-kun" (manufactured by Asahi Kasei Engineering Co., Ltd.)), and then calculating the particle diameter R using the following formula.
[0038]
number
[0039] The average particle size of the negative electrode active material in the negative electrode layer can be measured by specifying the negative electrode active material by its composition when measuring the above-mentioned chemical composition.
[0040] The volume proportion of the negative electrode active material in the negative electrode layer is not particularly limited, and from the viewpoint of further improving the utilization rate of the negative electrode active material, it is preferably from 20% to 80%, more preferably from 30% to 75%, and even more preferably from 30% to 60%.
[0041] The volume ratio of the negative electrode active material in the negative electrode layer can be measured from the SEM image after FIB cross-section processing. In detail, the cross-section of the negative electrode layer is observed using SEM-EDX. Elements contained only in the solid electrolyte are detected, and the area where the element is not detected can be regarded as the negative electrode active material. For example, if the solid electrolyte contains La and the electrode active material does not contain La, the area where W is detected by EDX and La is not detected is determined to be the negative electrode active material, and the area ratio of the above-mentioned area is calculated, thereby making it possible to measure the volume ratio of the negative electrode active material.
[0042] The particle shape of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, any of spherical, flat, and irregular particle shapes.
[0043] The solid electrolyte contained in the negative electrode layer is a solid electrolyte having a garnet structure. If the negative electrode layer contains another solid electrolyte (e.g., a Nasicon-type solid electrolyte) instead of the garnet-type solid electrolyte, the solid electrolyte reacts with the negative electrode active material during sintering, resulting in a decrease in the utilization rate of the negative electrode active material.
[0044] The term "solid electrolyte having a garnet-type structure" means that the solid electrolyte has a garnet-type crystal structure, and in a broad sense, means that the solid electrolyte has a crystal structure that can be recognized as a garnet-type crystal structure by a person skilled in the field of solid-state batteries. In a narrow sense, the term "solid electrolyte having a garnet-type structure" means that the solid electrolyte shows one or more main peaks corresponding to Miller indices specific to the so-called garnet-type crystal structure at a predetermined incidence angle in X-ray diffraction.
[0045] The garnet-type solid electrolyte is not particularly limited as long as it has a garnet-type crystal structure. From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, the garnet-type solid electrolyte preferably contains Li (lithium), La (lanthanum), Zr (zirconium) and O (oxygen), and more preferably further contains W.
[0046] Garnet-type solid electrolytes have the general formula (G): [ka]
[0047] In formula (G), A is one or more elements capable of forming a solid solution in the Li site of the oxide having the garnet-type crystal structure. More specifically, A is one or more elements selected from the group consisting of Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc), and Sc (scandium). From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, A is preferably one or more elements selected from the group consisting of Ga (gallium), Al (aluminum), and Sc (scandium), or is absent (i.e., x=0), more preferably contains Ga or is absent (i.e., x=0), and even more preferably is absent (i.e., x=0). When A contains Ga, A may contain a combination of Ga and one or more elements Ax selected from the group consisting of Al, Mg, Zn, and Sc (particularly the group consisting of Al and Sc). B I is one or more elements selected from the group consisting of elements that can take a trivalent valence among elements belonging to Groups 1 to 3 that can take an 8-coordination with oxygen. I Specifically, B is one or more elements selected from the group consisting of La (lanthanum), Y (yttrium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holminium), Er (erbium), Tm (thulium), Yb (ytterbium) and Lu (lutetium). I Preferably, B contains La (lanthanum) from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material. I From the same viewpoint, it is more preferable that the cathode material contains La (lanthanum). B IIis one or more elements selected from the group consisting of elements belonging to Groups 1 to 3 that can form eight-coordinated bonds with oxygen and can have a valence other than trivalent. II For details, see the bivalent B II Ca (calcium), Sr (strontium) and Ba (barium) as well as tetravalent B II and Ce (cerium) as the element of interest. II From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that there is no ion (that is, y=0). D I D is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming a tetravalent valence among typical elements belonging to groups 12 to 15. I Specifically, D is one or more elements selected from the group consisting of Zr (zirconium), Ti (titanium), Hf (hafnium), Ge (germanium) and Sn (tin). I Preferably, the material D contains Zr (zirconium) from the viewpoint of further suppressing side reactions during firing and a decrease in the ionic conductivity of the garnet-type oxide, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material. I From the same viewpoint, it is more preferable that the alloy contains Zr (zirconium). D II D is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming valences other than 4 among the typical elements belonging to groups 12 to 15. II For details, see trivalent D II Sc (Scandium) as 5-valent D II Ta (tantalum), Nb (niobium), Sb (antimony) and Bi (bismuth) as well as hexavalent D II The element is one or more selected from the group consisting of Mo (molybdenum), W (tungsten) and Te (tellurium). IIFrom the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, is preferably one or more elements selected from the group consisting of Nb (niobium), Ta (tantalum), W (tungsten), and Bi (bismuth), or is absent (i.e., z=0). D II From the same viewpoint, more preferably contains W (tungsten), and further preferably contains Ta (tantalum) and W (tungsten).
[0048] In formula (G), α satisfies 3.0≦α≦8.0, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, preferably satisfies 5.5≦α≦7.0, more preferably 6.0≦α≦6.8, even more preferably 6.2≦α≦6.8, and particularly preferably 6.2≦α≦6.7. β satisfies 2.5≦β≦3.5, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it preferably satisfies 2.6≦β≦3.4, more preferably 2.7≦β≦3.3, even more preferably 2.8≦β≦3.2, particularly preferably 2.9≦β≦3.1, and is most preferably 3.0. I When contains two or more elements, "β-y" is the sum of the numbers for each element. γ satisfies 1.5≦γ≦2.5, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, preferably satisfies 1.6≦γ≦2.4, more preferably satisfies 1.7≦γ≦2.3, even more preferably satisfies 1.8≦γ≦2.2, particularly preferably satisfies 1.9≦γ≦2.1, and is most preferably 2.0. I When contains two or more elements, "γ-z" is the total number of the elements. "γ-z" is usually 1.0 to 2.5, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferably 1.2 to 2.2, more preferably 1.3 to 1.7. ω satisfies 11≦ω≦13, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it preferably satisfies 11≦ω≦12.5, more preferably 11.5≦ω≦12.5, and further preferably is "12-σ". δ indicates the amount of oxygen vacancy and may be 0. δ usually satisfies 0≦δ<1. The amount of oxygen vacancy δ may be considered to be 0 because it cannot be quantitatively analyzed even using the latest equipment. x satisfies 0≦x≦1.0, and from the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, preferably satisfies 0≦x≦0.8, more preferably satisfies 0≦x≦0.6, even more preferably satisfies 0≦x≦0.4, particularly preferably satisfies 0≦x≦0.2, and most preferably is 0. When A contains two or more elements, the total number of x for each element (i.e., the number corresponding to x for each element) may be within the above range of x. When A contains two or more elements, each of x for each element (i.e., the number corresponding to x for each element) may be independently 0.01 or more and 0.5 or less, particularly 0.03 or more and 0.18 or less. In particular, when A contains a combination of Ga and one or more elements Ax selected from the group consisting of Al, Mg, Zn, and Sc (particularly the group consisting of Al and Sc), x for Ga (hereinafter, x Ga ) and x with respect to Ax (hereafter, x Ax From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that the above-mentioned range is as follows: x Ga is between 0.01 and 0.3, in particular between 0.03 and 0.18; x Ax is 0.01 to 0.3, particularly 0.03 to 0.18; when Ax contains two or more elements, x for each element is Ax (i.e., x for each element Ax The total number of the above x Ax It is sufficient if the range is within the range. y is a value smaller than β, and usually satisfies 0≦y≦1.0. From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, y preferably satisfies 0≦y≦0.8, more preferably 0≦y≦0.6, even more preferably 0≦y≦0.4, particularly preferably 0≦y≦0.2, and most preferably 0. II When contains two or more elements, the total number of y for each element (that is, the number corresponding to y for each element) may be within the above range of y. z is a value equal to or less than γ, and usually satisfies 0≦z≦2.2. From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it preferably satisfies 0≦z≦2.0, more preferably 0≦z≦1.0, further preferably 0.2≦z≦0.8, and particularly preferably satisfies 0.3≦z≦0.6. II When contains two or more elements, the total number of z for each element (i.e., the number corresponding to z for each element) may be within the above range of z. II When D contains two or more elements, each z for each element (i.e., the number corresponding to z for each element) may be independently 0.01 or more and 1.0 or less, particularly 0.05 or more and 0.5 or less. II If contains Ta and W, z with respect to Ta (hereinafter z Ta ) and z with respect to W (hereafter, z W From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that the above-mentioned range is as follows: z Ta is between 0.1 and 1.0, in particular between 0.2 and 0.6; z W is 0.01 or more and 0.5 or less, particularly 0.08 or more and 0.2 or less.
[0049] Specific examples of the garnet-type solid electrolyte represented by the general formula (G) include, for example, Li 6.6 La3(Zr 1.6 Ta 0.4 )O 12 , (Li 6.4 Ga 0.05 Al 0.15 )La3Zr2O 12, (Li 6.4 Al 0.2 )La3Zr2O 12 , (Li 6.4 Ga 0.15 Sc 0.05 )La3Zr2O 12 , Li 6.75 La3(Zr 1.75 Nb 0.25 )O 12 , Li 6.4 La3(Zr 1.5 Ta 0.4 W 0.1 )O 12 , Li 6.3 La3(Zr 1.45 Ta 0.4 W 0.15 )O 12 , Li 6.53 La3(Zr 1.53 Ta 0.4 Bi 0.07 )O 12 etc.
[0050] The chemical composition of the solid electrolyte may be an average chemical composition. The average chemical composition of the solid electrolyte (particularly a solid electrolyte having a garnet-type structure) in the negative electrode layer means the average value of the chemical composition of the solid electrolyte in the thickness direction of the negative electrode layer. The average chemical composition of the solid electrolyte can be analyzed and measured by breaking the solid battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the negative electrode layer using SEM-EDX. In the negative electrode layer, the average chemical composition of the negative electrode active material and the average chemical composition of the solid electrolyte can be measured separately based on their compositions in the composition analysis.
[0051] The solid electrolyte of the negative electrode layer can be obtained by the same method as that for the negative electrode active material, except that a raw material compound containing a predetermined metal atom is used, or can be obtained as a commercially available product.
[0052] The chemical composition and crystal structure of the solid electrolyte in the anode layer usually remain almost unchanged by sintering, and the solid electrolyte preferably has the above average chemical composition and crystal structure in the solid-state battery after sintering the anode layer together with the cathode layer and the solid electrolyte layer.
[0053] The volume ratio of the solid electrolyte having a garnet-type structure in the negative electrode layer is not particularly limited, and from the viewpoint of a balance between further improving the utilization rate of the negative electrode active material and increasing the energy density of the solid-state battery, it is preferably from 10% to 50%, and more preferably from 20% to 40%.
[0054] The volume ratio of the garnet-type solid electrolyte in the negative electrode layer can be measured by the same method as the volume ratio of the negative electrode active material. The garnet-type solid electrolyte can be determined by detecting the elements contained in the garnet-type solid electrolyte by EDX or the like. For example, when the solid electrolyte contains Zr or La, it is determined based on the portion where Zr and / or La are detected by EDX.
[0055] The present invention does not preclude the negative electrode layer from containing a solid electrolyte other than the garnet-type solid electrolyte as the solid electrolyte. From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, it is preferable that the negative electrode layer does not contain any other solid electrolyte.
[0056] In the present invention, the negative electrode layer contains a combination of the above-mentioned negative electrode active material and the above-mentioned garnet-type solid electrolyte, so that the reaction between the negative electrode active material and the garnet-type solid electrolyte can be sufficiently suppressed, and as a result, the decrease in the utilization rate of the negative electrode active material can be sufficiently suppressed.
[0057] From the viewpoint of further suppressing the reaction between the solid electrolyte and the negative electrode active material, in each of the more preferred embodiment A, the further preferred embodiment B, and the most preferred embodiment C, the negative electrode layer contains the following negative electrode active material and garnet-type solid electrolyte in combination:
[0058] Implementation A Negative electrode active material A: Among the above-mentioned negative electrode active materials, a negative electrode active material having a chemical composition represented by the same general formula as the above-mentioned general formula (N) and having a single-phase structure of a high-temperature phase Li4WO5 type structure. In other words, the negative electrode active material A may be a negative electrode active material having a chemical composition represented by the above general formula (N) and having a single-phase structure of a high-temperature phase Li4WO5 type crystal structure. Garnet-type solid electrolyte A: A garnet-type solid electrolyte having a chemical composition represented by the above general formula (G).
[0059] Implementation Example B Negative electrode active material B: Among the above-mentioned negative electrode active materials, a negative electrode active material having the following chemical composition and a single-phase structure of a high-temperature phase Li4WO5 type structure: Chemical composition: A chemical composition represented by the same general formula as the above general formula (N), except that α / β satisfies 3.8≦α / β≦6.5 and M is W. In other words, the negative electrode active material B may be a negative electrode active material in which, in the above general formula (N), α / β satisfies 3.8≦α / β≦6.5 and M is W, and which has a single-phase structure of a high-temperature phase Li4WO5-type crystal structure. Garnet-type solid electrolyte B: Among the above-mentioned garnet-type solid electrolytes, a garnet-type solid electrolyte having the following chemical composition: Chemical composition=Chemical composition represented by the same general formula as the above general formula (G) except that condition (s1) is satisfied: Condition (s1): A includes Ga or does not include Ga (i.e., x=0). For example, x=0 or A includes Ga and does not include Ga. <x≦1.0であってもよい。 In other words, the garnet-type solid electrolyte B may be a garnet-type solid electrolyte that satisfies the above condition (s1) in the above general formula (G).
[0060] Implementation C Negative electrode active material C: Among the above-mentioned negative electrode active materials, a negative electrode active material having the following chemical composition and a single-phase structure of a high-temperature phase Li4WO5 type structure: Chemical composition: A chemical composition represented by the same general formula as the above general formula (N), except that α / β satisfies 3.8≦α / β≦6.5 and M is W. In other words, the negative electrode active material C may be a negative electrode active material in which, in the above general formula (N), α / β satisfies 3.8≦α / β≦6.5 and M is W, and which has a single-phase structure of a high-temperature phase Li4WO5-type crystal structure. Garnet-type solid electrolyte C: Among the above-mentioned garnet-type solid electrolytes, a garnet-type solid electrolyte having the following chemical composition: Chemical composition=a chemical composition represented by the same general formula as the above general formula (G) except that the condition (s1) and the condition (s2) are satisfied: Condition (s1): A includes Ga or does not include Ga (i.e., x=0); for example, x=0 or A includes Ga and does not include Ga. <x≦1.0であってもよい。 Condition(s2):D II Includes Ta (tantalum) and W (tungsten). In other words, the garnet-type solid electrolyte C may be a garnet-type solid electrolyte that satisfies the above conditions (s1) and (s2) in the above general formula (G).
[0061] The negative electrode layer may further include a sintering aid and / or a conductive aid.
[0062] By including a sintering aid in the negative electrode layer, densification is possible even during sintering at a lower temperature, and element diffusion at the negative electrode active material / solid electrolyte layer interface can be suppressed. As the sintering aid, a sintering aid known in the field of solid-state batteries can be used. From the viewpoint of further improving the utilization rate of the negative electrode active material, the inventors have conducted studies and found that the composition of the sintering aid contains at least Li (lithium), B (boron), and O (oxygen), and the molar ratio of Li to B (Li / B) is preferably 2.0 or more. These sintering aids have a low melting point, and by proceeding with liquid phase sintering, the negative electrode layer can be densified at a lower temperature. In addition, by using the above composition, the side reaction between the sintering aid and the garnet-type solid electrolyte during sintering can be further suppressed. Examples of sintering aids that satisfy these requirements include Li3BO3, (Li 2.7 Al 0.3 )BO3, Li 2.4 Al 0.2 BO3, Li 2.8 (B 0.8 C 0.2 Among these, Li has particularly high ionic conductivity. 2.4 Al 0.2 It is particularly preferred to use BO3.
[0063] The volume proportion of the sintering aid in the negative electrode layer is not particularly limited, and from the viewpoint of a balance between further improving the utilization rate of the negative electrode active material and increasing the energy density of the solid-state battery, it is preferably 0.1% or more and 10% or less, and more preferably 1% or more and 7% or less.
[0064] The volume ratio of the sintering aid in the negative electrode layer can be measured by the same method as the volume ratio of the negative electrode active material. When the above sintering aid is used, B (boron) can be detected by EDX and it can be determined that the area is the sintering aid.
[0065] In the negative electrode layer, the conductive assistant may be a conductive assistant known in the field of solid-state batteries. From the viewpoint of further improving ion conductivity and further suppressing the growth of Li dendrites, examples of conductive assistants that are preferably used include metal materials such as Ag (silver), Au (gold), Pd (palladium), Pt (platinum), Cu (copper), Sn (tin), and Ni (nickel); and carbon materials such as carbon nanotubes such as acetylene black, Ketjen black, Super P (registered trademark), and VGCF (registered trademark). The shape of the carbon material is not particularly limited, and any shape such as a spherical shape, a plate shape, or a fibrous shape may be used.
[0066] The volume ratio of the conductive assistant in the negative electrode layer is not particularly limited, and from the viewpoint of further improving the utilization rate of the active material, it is preferably from 10% to 50%, and more preferably from 20% to 40%.
[0067] The thickness of the negative electrode layer is usually 2 to 100 μm, and from the viewpoint of further improving the utilization rate of the active material, preferably 1 to 30 μm. The thickness of the negative electrode layer is the average value of thicknesses measured at any 10 points in an SEM image.
[0068] In the negative electrode layer, the porosity is not particularly limited, and from the viewpoint of further improving the utilization rate of the active material, it is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.
[0069] The porosity of the negative electrode layer was measured from an SEM image after FIB cross-section processing.
[0070] In the negative electrode layer, the negative electrode active material and the solid electrolyte (and the conductive assistant and sintering assistant, if desired) may have the form of a sintered body. For example, when the negative electrode layer contains the negative electrode active material, the solid electrolyte, the conductive assistant, and the sintering assistant, the negative electrode layer may have the form of a sintered body in which the negative electrode active material particles are bonded to each other by the solid electrolyte, the conductive assistant, and the sintering assistant, while the negative electrode active material particles, the solid electrolyte, the conductive assistant, and the sintering assistant are bonded to each other by sintering.
[0071] (Positive electrode layer) In the present invention, the positive electrode layer is not particularly limited. For example, the positive electrode layer includes a positive electrode active material. The positive electrode layer may have the form of a sintered body including positive electrode active material particles.
[0072] The positive electrode layer is a layer capable of absorbing and releasing metal ions, preferably a layer capable of absorbing and releasing lithium ions. The positive electrode active material is not particularly limited, and positive electrode active materials known in the field of solid-state batteries can be used. Examples of the positive electrode active material include lithium-containing phosphate compound particles having a Nasicon structure, lithium-containing phosphate compound particles having an olivine structure, lithium-containing layered oxide particles, and lithium-containing oxide particles having a spinel structure. Specific examples of lithium-containing phosphate compounds having a Nasicon structure that are preferably used include Li3V2(PO4)3, etc. Specific examples of lithium-containing phosphate compounds having an olivine structure that are preferably used include LiFePO4, LiMnPO4, etc. Specific examples of lithium-containing layered oxide particles that are preferably used include LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 Specific examples of lithium-containing oxides having a spinel structure that are preferably used include LiMn2O4, LiNi 0.5 Mn 1.5 O4, Li4Ti5O 12 The positive electrode active material is LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 It is more preferable to use a lithium-containing layered oxide such as O2. Only one type of these positive electrode active material particles may be used, or a mixture of two or more types may be used.
[0073] The positive electrode active material in the positive electrode layer has a Nasicon structure, which means that the positive electrode active material (particularly its particles) has a Nasicon crystal structure, and in a broader sense, means that the positive electrode active material has a crystal structure that can be recognized as a Nasicon crystal structure by those skilled in the art of solid-state batteries. In a narrower sense, the positive electrode active material in the positive electrode layer has a Nasicon structure, which means that the positive electrode active material (particularly its particles) shows one or more main peaks in X-ray diffraction at a specified incident angle, which correspond to Miller indices specific to the so-called Nasicon crystal structure. The compounds exemplified above are preferably used as positive electrode active materials having a Nasicon structure.
[0074] The positive electrode active material in the positive electrode layer has an olivine structure, which means that the positive electrode active material (particularly its particles) has an olivine crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as an olivine crystal structure by those skilled in the art of solid-state batteries. In a narrow sense, the positive electrode active material in the positive electrode layer has an olivine structure, which means that the positive electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called olivine crystal structure at a predetermined incidence angle in X-ray diffraction. The above-mentioned compounds can be given as examples of the positive electrode active material having an olivine structure that is preferably used.
[0075] The positive electrode active material in the positive electrode layer has a spinel structure, which means that the positive electrode active material (particularly its particles) has a spinel crystal structure, and in a broad sense, means that the positive electrode active material has a crystal structure that can be recognized as a spinel crystal structure by a person skilled in the field of solid-state batteries. In a narrow sense, the positive electrode active material in the positive electrode layer has a spinel structure, which means that the positive electrode active material (particularly its particles) shows one or more main peaks corresponding to Miller indices specific to the so-called spinel crystal structure at a predetermined incidence angle in X-ray diffraction. The above-mentioned compounds can be given as examples of the positive electrode active material having a spinel structure that is preferably used.
[0076] The chemical composition of the positive electrode active material may be an average chemical composition. The average chemical composition of the positive electrode active material means the average value of the chemical composition of the positive electrode active material in the thickness direction of the positive electrode layer. The average chemical composition of the positive electrode active material can be analyzed and measured by breaking the solid-state battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the positive electrode layer using SEM-EDX.
[0077] The positive electrode active material can be obtained in the same manner as the negative electrode active material, except that a raw material compound containing a predetermined metal atom is used, or can be obtained as a commercially available product.
[0078] The chemical composition and crystal structure of the positive electrode active material in the positive electrode layer usually remain substantially unchanged by sintering. The positive electrode active material may have the above-mentioned chemical composition and crystal structure in the solid-state battery after sintering the positive electrode layer together with the negative electrode layer and the solid electrolyte layer.
[0079] The average particle size of the positive electrode active material is not particularly limited and may be, for example, 0.01 μm or more and 10 μm or less, and preferably 0.05 μm or more and 4 μm or less.
[0080] The average particle size of the positive electrode active material can be determined by the same method as that for the average particle size of the negative electrode active material in the negative electrode layer.
[0081] The average particle size of the positive electrode active material in the positive electrode layer is directly reflected by the average particle size of the positive electrode active material used during production, especially when LCO is used for the positive electrode particles.
[0082] The particle shape of the positive electrode active material in the positive electrode layer is not particularly limited, and may be, for example, any of spherical, flat, and irregular shapes.
[0083] The volume ratio of the positive electrode active material in the positive electrode layer is not particularly limited, but is preferably 30% or more and 90% or less, and more preferably 40% or more and 70% or less.
[0084] The positive electrode layer may further contain, in addition to the positive electrode active material, for example, a solid electrolyte, a sintering aid, and / or a conductive aid.
[0085] The type of solid electrolyte contained in the positive electrode layer is not particularly limited. For example, a solid electrolyte having a garnet structure (Li 6.4 Ga 0.2 )La3Zr2O 12 , Li 6.4 La3(Zr 1. 6Ta 0.4 )O 12 , (Li 6.4 Al 0.2 )La3Zr2O 12 , Li 6.5 La3(Zr 1.5 Mo 0.25 )O 12 , a solid electrolyte Li with a LISICON-type structure 3+x (V 1-x S x )O4, a solid electrolyte with a perovskite structure, La 2 / 3-x Li 3x Examples of such electrolytes include TiO3, solid electrolytes having an amorphous structure Li3BO3-Li4SiO4, etc. Among these, it is particularly preferable to use a solid electrolyte having a garnet type structure or a solid electrolyte having a LISICON type structure.
[0086] The solid electrolyte for the positive electrode layer can be obtained in the same manner as for the negative electrode active material, except that a raw material compound containing a predetermined metal atom is used, or can be obtained as a commercially available product.
[0087] The chemical composition and crystal structure of the solid electrolyte in the positive electrode layer typically remains substantially unchanged by sintering, and the solid electrolyte may have the average chemical composition and crystal structure described above in the solid-state battery after sintering the positive electrode layer together with the negative electrode layer and the solid electrolyte layer.
[0088] The volume ratio of the solid electrolyte in the positive electrode layer is not particularly limited, but is preferably 20% to 60%, more preferably 30% to 45%, from the viewpoint of a balance for increasing the energy density of the solid battery.
[0089] As the sintering aid in the positive electrode layer, the same compounds as the sintering aid in the negative electrode layer can be used.
[0090] The volume ratio of the sintering aid in the positive electrode layer is not particularly limited, but from the viewpoint of a balance for increasing the energy density of the solid-state battery, it is preferably 0.1% or more and 20% or less, and more preferably 1% or more and 10% or less.
[0091] As the conductive assistant in the positive electrode layer, the same compounds as the conductive assistant in the negative electrode layer can be used.
[0092] The volume ratio of the conductive assistant in the positive electrode layer is not particularly limited, and from the viewpoint of a balance for increasing the energy density of the solid-state battery, it is preferably from 10% to 50%, and more preferably from 20% to 40%.
[0093] In the positive electrode layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.
[0094] The porosity of the positive electrode layer is a value measured in the same manner as the porosity of the negative electrode layer.
[0095] (Solid electrolyte layer) In the present invention, the solid electrolyte layer is not particularly limited. The solid electrolyte layer preferably contains a solid electrolyte having a garnet structure from the viewpoint of further suppressing side reactions during firing with the negative electrode active material and further improving the utilization rate of the active material. The solid electrolyte layer may have the form of a sintered body containing the solid electrolyte.
[0096] The garnet-type solid electrolyte contained in the solid electrolyte layer is the same as the solid electrolyte having a garnet-type structure contained in the negative electrode layer, and may be selected from the same range as the solid electrolyte having a garnet-type structure described in the description of the negative electrode layer. When both the solid electrolyte layer and the negative electrode layer contain solid electrolytes having a garnet-type structure, the solid electrolyte having a garnet-type structure contained in the solid electrolyte layer and the solid electrolyte having a garnet-type structure contained in the negative electrode layer may have the same chemical composition or may have different chemical compositions.
[0097] The garnet-type solid electrolyte contained in the solid electrolyte layer is not particularly limited as long as it has a garnet-type crystal structure, and preferably has a chemical composition within the range of the chemical composition represented by the above general formula (G) similar to the garnet-type solid electrolyte contained in the negative electrode layer. When the solid electrolyte layer contains a solid electrolyte having this chemical composition, it is possible to achieve a further improvement in the utilization rate of the negative electrode active material in the interface region between the negative electrode layer and the solid electrolyte layer.
[0098] The chemical composition of the solid electrolyte in the solid electrolyte layer may be an average chemical composition. The average chemical composition of the solid electrolyte (particularly a solid electrolyte having a garnet-type structure) in the solid electrolyte layer means the average value of the chemical composition of the solid electrolyte in the thickness direction of the solid electrolyte layer. The average chemical composition of the solid electrolyte can be analyzed and measured by breaking the solid battery and performing composition analysis by EDX (energy dispersive X-ray spectroscopy) in a field of view that includes the entire thickness direction of the solid electrolyte layer using SEM-EDX (energy dispersive X-ray spectroscopy).
[0099] The chemical composition and crystal structure of the solid electrolyte in the solid electrolyte layer usually remain substantially unchanged by sintering, and the solid electrolyte may have the above-mentioned chemical composition and crystal structure in the solid-state battery after the solid electrolyte layer is sintered together with the anode layer and the cathode layer.
[0100] The volume ratio of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is preferably 10% or more and 100% or less, more preferably 20% or more and 100% or less, and even more preferably 30% or more and 100% or less.
[0101] The volume proportion of the solid electrolyte in the solid electrolyte layer can be measured by the same method as for the volume proportion of the solid electrolyte in the negative electrode layer.
[0102] The solid electrolyte layer may further contain, for example, a sintering aid in addition to the solid electrolyte. At least one of the negative electrode layer and the solid electrolyte layer, preferably both, preferably further contains a sintering aid. At least one of the negative electrode layer and the solid electrolyte layer further contains a sintering aid means that either one of the negative electrode layer and the solid electrolyte layer may further contain a sintering aid, or both of them may further contain a sintering aid.
[0103] As the sintering aid in the solid electrolyte layer, the same compounds as the sintering aid in the negative electrode layer can be used.
[0104] The volume proportion of the sintering aid in the solid electrolyte layer is not particularly limited, and from the viewpoint of a balance between further improving the utilization rate of the negative electrode active material and increasing the energy density of the solid battery, it is preferably 0.1% or more and 20% or less, and more preferably 1% or more and 10% or less.
[0105] The thickness of the solid electrolyte layer is usually 0.1 μm or more and 30 μm or less, and from the viewpoint of making the solid electrolyte layer thinner, it is preferably 1 μm or more and 20 μm or less.
[0106] The thickness of the solid electrolyte layer is the average value of thicknesses measured at 10 arbitrary points in the SEM image.
[0107] In the solid electrolyte layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.
[0108] The porosity of the solid electrolyte layer is a value measured in the same manner as the porosity of the negative electrode layer.
[0109] The solid-state battery of the present invention may further include any of the components that a conventional solid-state battery may include, such as a positive electrode current collecting layer, a negative electrode current collecting layer, a protective layer, an end electrode, and the like.
[0110] [Solid-state battery manufacturing method] The solid-state battery can be manufactured, for example, by the so-called green sheet method, the printing method or a combination of these methods.
[0111] The green sheet method will now be described. First, a paste is prepared by appropriately mixing a solvent, a binder, etc. with a positive electrode active material. The paste is applied onto a sheet and dried to form a first green sheet for forming a positive electrode layer. The first green sheet may contain a solid electrolyte, a conductive additive, and / or a sintering additive, etc.
[0112] A paste is prepared by appropriately mixing the negative electrode active material with a solid electrolyte, a solvent, a binder, etc. The paste is applied onto a sheet and dried to form a second green sheet for forming the negative electrode layer. The second green sheet may contain a conductive additive and / or a sintering additive, etc.
[0113] A paste is prepared by appropriately mixing the solid electrolyte with a solvent, a binder, etc. The paste is applied and dried to prepare a third green sheet for forming the solid electrolyte layer. The third green sheet may contain a sintering aid, etc.
[0114] The solvent and binder for producing the first to third green sheets are not particularly limited. For example, a solvent that can be used in the manufacture of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid batteries is used as the solvent. A specific example of the solvent is usually a solvent that can use the binder described below. For example, an alcohol such as 2-propanol is used as such a solvent. For example, a binder that can be used in the manufacture of a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid batteries is used as the binder. Specific examples of such binders include butyral resin, acrylic resin, and the like.
[0115] Next, the first to third green sheets are appropriately laminated to prepare a laminate. The laminate thus prepared may be pressed. A preferred pressing method is hydrostatic pressing. After that, the laminate is heated to a temperature of, for example, 300°C to 500°C to remove the binder, and then sintered at 600 to 900°C to obtain a solid-state battery.
[0116] The printing method is explained below. The term "printing" is used as a concept that includes coating. The printing method is similar to the green sheet method, except for the following: Prepare ink for each layer having the same composition as the paste for each layer used to obtain the green sheet, except that the amounts of solvent and resin are suitable for use as an ink. · Each layer is printed using ink and laminated to create a laminate.
[0117] The present invention will be described in more detail below based on specific examples. However, the present invention is not limited to the following examples and can be modified as appropriate within the scope of the present invention. EXAMPLES
[0118] <Experimental Example 1> (Production of garnet-type solid electrolyte) The raw materials including lithium hydroxide monohydrate (LiOH·H2O), lanthanum hydroxide (La(OH)3), zirconium oxide (ZrO2), and tantalum oxide (Ta2O5) were weighed so that the composition of the solid electrolyte was as shown in Table 1. Next, water was added, and the mixture was sealed in a 100 ml polyethylene polypot and rotated on a pot rack at 150 rpm for 16 hours to mix the raw materials. In addition, the lithium source, lithium hydroxide monohydrate LiOH·H2O, was charged in an amount 3 mass% in excess of the target composition, taking into account Li deficiency during sintering. Next, the obtained slurry was dried and then pre-sintered in oxygen gas at 900°C for 5 hours. After that, a mixed solvent of toluene and acetone was added to the obtained pre-sintered material, which was then pulverized in a planetary ball mill for 6 hours and then dried to obtain a solid electrolyte powder with the composition shown in Table 1.
[0119] (Manufacturing Nasicon-type solid electrolytes) Raw materials including lithium carbonate (Li2CO3), aluminum oxide (Al2O3), germanium oxide (GeO2), and ammonium dihydrogen phosphate ((NH4)H2PO4) were weighed so that the composition of the solid electrolyte was as shown in Table 1, and mixed well in a mortar. The mixture was calcined at 400°C for two hours in an air atmosphere. Water was added to the calcined powder, which was then sealed in a 100 ml polyethylene polypot and rotated on a pot rack at 150 rpm for 16 hours to crush the calcined powder. Next, the obtained slurry was dried and then calcined at 850°C for five hours in oxygen gas. After that, a mixed solvent of toluene and acetone was added to the obtained calcined product, which was then pulverized in a planetary ball mill for six hours and then dried to obtain a solid electrolyte powder with the composition shown in Table 1.
[0120] (Production of electrode active material) Raw materials including lithium carbonate (Li2CO3) and tungsten oxide (WO3) were weighed so that the composition of the negative electrode active material had a Li / W ratio shown in Table 1, and were thoroughly mixed in a mortar. For Example 3, the materials were weighed so that the Li / W ratio was 6.0. Next, ethanol was added, the mixture was sealed in a 100 ml polyethylene polypot, and the mixture was rotated on a pot rack at 150 rpm for 16 hours to mix the raw materials. After drying the obtained slurry, sintering was performed in air under the following conditions. The negative electrode active materials of Comparative Examples 1 and 2 and Example 2 were sintered at 650°C for 5 hours. The negative electrode active materials of Comparative Example 4 and Examples 1 and 3 were sintered at 750°C for 5 hours. Thereafter, a mixed solvent of toluene and acetone was added to the obtained sintered product, which was then pulverized in a planetary ball mill for 6 hours and then dried to obtain the negative electrode active material powders shown in Table 1. The electrode active material (purity 99% or more) having the composition shown in Comparative Example 3 was obtained by pulverizing a commercially available product in a planetary ball mill for 6 hours and then drying it.
[0121] (Examples 1 to 3 and Comparative Examples 1 to 4) The solid electrolyte and electrode active material shown in Table 1 were mixed and sintered at 800° C. to obtain a sample, which was then analyzed by XRD to evaluate the presence or absence of decomposition of the solid electrolyte and electrode active material. If no peaks due to both the solid electrolyte and the electrode active material, or either one of them, were observed after sintering, it was judged as "decomposition occurred," and if peaks due to both the solid electrolyte and the electrode active material were observed after sintering, it was judged as "no decomposition."
[0122] FIG. 1 shows the XRD patterns after sintering of Comparative Example 1 and Example 1, and the XRD pattern of either the solid electrolyte or the electrode active material after sintering. From Comparative Example 1, when an electrode active material with a Li / W ratio of 2 was used, the peak derived from the garnet-type solid electrolyte completely disappeared after sintering, and it was found that the solid electrolyte was decomposed during sintering. When an active material with a Li / W ratio of 2 or less was used, it was found that the garnet-type solid electrolyte was decomposed during sintering (Table 1). When a negative electrode active material with a Li / W ratio of 2 was used as in Comparative Example 1, it is considered that the decomposition of the solid electrolyte (LLZ) progressed due to sintering, and La2Zr2O7 with no ion conductivity was produced.
[0123] From Example 1, when an electrode active material with a Li / W ratio of more than 2 (e.g., 4) is used, peaks derived from both the electrode active material and the garnet-type solid electrolyte are observed after sintering, and it was found that side reactions between the two do not easily proceed. As in Example 1, when a negative electrode active material with a Li / W ratio of more than 2 (e.g., 4) is used, it was found that both the negative electrode active material and the solid electrolyte (LLZ) remain even after sintering. Since side reactions do not easily proceed during sintering, good charge / discharge characteristics are easily obtained.
[0124] From the above, it was found that when an electrode active material with a Li / W ratio of more than 2 is used, side reactions during sintering with the garnet-type solid electrolyte can be extremely suppressed. From Comparative Example 4, it was found that when a NASICON type solid electrolyte was used as the solid electrolyte, the reaction proceeded even when an electrode active material with a Li / W ratio of more than 2 was used. Therefore, it was found that the effects of the present invention can be obtained by combining an electrode active material having a Li / W ratio of more than 2 with a garnet-type solid electrolyte.
[0125] [Table 1]
[0126] In Table 1, "high-temperature phase Li4WO5" means "single-phase structure of high-temperature phase Li4WO5 type crystal structure." The crystal structures were determined by the above-mentioned method based on the peaks specific to each crystal structure and their intensities in X-ray diffraction (XRD using CuKα radiation). The same applies to Tables 2 and 3 below.
[0127] <Experimental Example 2> (Production of garnet-type solid electrolyte) A solid electrolyte powder having the composition shown in Table 2 was obtained by the same method as the method for producing a garnet-type solid electrolyte in Experimental Example 1, except that the raw materials were selected and weighed so that the composition of the garnet-type solid electrolyte would be as shown in Table 2. The raw materials used were the same as those described in "Production of garnet-type solid electrolyte" in Experimental Example 1, as well as gallium oxide (Ga2O3), aluminum oxide (Al2O3), scandium oxide (Sc2O3), niobium oxide (Nb2O5), tungsten oxide (WO3), and bismuth oxide (Bi2O3).
[0128] (Production of negative electrode active material) Raw materials including lithium carbonate (Li2CO3), tungsten oxide (WO3), molybdenum oxide (MoO3), zirconium oxide (ZrO2), tantalum oxide (Ta2O5), and magnesium oxide (MgO) were weighed out so that the composition of the negative electrode active material had the element ratio shown in Table 2. For Example 6, the materials were weighed out so that the Li / W ratio was 3.7. For Example 7, the materials were weighed out so that the Li / W ratio was 6.0. For Example 11, the materials were weighed out so that the Li / W ratio was 4.4. Next, ethanol was added, the materials were sealed in a 100 ml polyethylene polypot, and the materials were rotated on a pot rack at 150 rpm for 16 hours to mix the raw materials. After drying the obtained slurry, sintering was performed in the air under the following conditions. The negative electrode active materials of Comparative Examples 5 and 6 and Examples 5 and 6 were sintered at 650°C for 5 hours. The negative electrode active materials of Comparative Example 4 and Examples 4, 7, 8, 9, 10, 11, and 12 were sintered at 750° C. for 5 hours. Then, a mixed solvent of toluene and acetone was added to the obtained sintered material, which was then pulverized in a planetary ball mill for 6 hours and then dried to obtain the negative electrode active material powders shown in Table 1. The electrode active material (purity 99% or more) having the composition shown in Comparative Example 7 was obtained by pulverizing a commercially available product in a planetary ball mill for 6 hours and then drying it.
[0129] (Manufacturing of solid electrolyte layers (garnet-type solid electrolyte substrates)) The composition of the garnet-type solid electrolyte is "(Li 6.4 Ga 0.05 Al 0.15 )La3Zr2O 12 The garnet-type solid electrolyte was produced in the same manner as in Experimental Example 1, except that the raw materials were selected and weighed so that "(Li 6.4 Ga 0.05 Al 0.15 )La3Zr2O 12 A garnet-type solid electrolyte powder having the composition " was obtained. The obtained garnet-type solid electrolyte powder, butyral resin, and alcohol were mixed in a mass ratio of 200:15:140, and then the alcohol was removed on a hot plate at 80°C to obtain a solid electrolyte powder coated with butyral resin as a binder. Next, the solid electrolyte powder coated with butyral resin was pressed into a tablet shape at 90 MPa using a tablet molding machine. The obtained solid electrolyte tablet was sufficiently covered with mother powder and sintered at a temperature of 500°C in an oxygen atmosphere to remove the butyral resin, and then sintered at about 1200°C for 3 hours in an oxygen atmosphere. Then, the temperature was lowered to obtain a sintered body of the solid electrolyte. The surface of the obtained sintered body was polished to obtain a garnet-type solid electrolyte substrate (solid electrolyte layer).
[0130] (Production of sintering aid powder) Lithium hydroxide monohydrate (LiOH·H2O), boron oxide (B2O3), and aluminum oxide (Al2O3) were weighed out appropriately, mixed in a mortar, and then pre-sintered at 650°C for 5 hours. The pre-sintered powder obtained was crushed and mixed in a mortar, and then sintered at 680°C for 40 hours. A mixed solvent of toluene and acetone was added to the obtained sintered powder, which was then crushed in a planetary ball mill for 6 hours and dried to obtain a powder with the composition formula Li 2.4 Al 0.2 A sintering aid powder represented by BO3 was prepared.
[0131] (Examples 4 to 12 and Comparative Examples 5 to 7: Production of Solid-State Batteries) The solid electrolyte powder, the negative electrode active material powder, the sintering aid powder, and the conductive aid powder (Ag particles) shown in Table 2 were weighed out to a volume ratio of 35:30:5:30, and mixed with alcohol and a binder to prepare a negative electrode layer paste. Next, the negative electrode layer paste was applied onto a solid electrolyte layer (i.e., a solid electrolyte substrate) and dried to obtain a laminate. The laminate was heated to 400°C to remove the binder, and then heat-treated at 800°C for 2 hours in an air atmosphere to prepare a laminate of a solid electrolyte layer and a negative electrode layer. Then, metallic lithium was attached as a counter electrode and reference electrode on the surface of the solid electrolyte layer of the laminate opposite to the surface of the negative electrode layer side, and the resultant was sealed in a 2032-type coin cell to produce a solid battery.
[0132] (Evaluation of solid-state batteries; utilization rate of negative electrode active material) The solid-state batteries produced in each of the comparative examples and examples were evaluated at 25° C. as follows. Charging was performed at a constant current and constant potential, with the lower limit potential being 0.2 V (vs. Li / Li + The charge termination condition was the point when the charge current decayed to 0.02 C. Discharge was performed at a constant current, and the discharge termination potential was 3.0 V (vs. Li / Li + ) was used. The constant current value of the charge and discharge currents was 0.1 C. The utilization rate of the negative electrode active material was calculated from the measured initial reversible capacity and the theoretical value of the initial reversible capacity according to the following formula, and was evaluated according to the following criteria. The theoretical value of the initial reversible capacity was taken as the amount of electricity when a two-electron reaction proceeded with respect to W. In addition, the charge in the present invention corresponds to a reduction reaction in which lithium ions are inserted into the negative electrode active material, and the discharge corresponds to an oxidation reaction in which lithium ions are desorbed from the negative electrode active material.
[0133]
number
[0134] ◎◎;80% or more (best); ◎; 72% or more but less than 80% (excellent); ○; 60% or more but less than 72% (good); △: 50% or more but less than 60% (no problem in practical use); ×: Less than 50% (problems in practical use).
[0135] Description of Figures 2A and 2B 2A and 2B show charge / discharge curves of the solid-state batteries prepared in Example 4 and Comparative Example 2, respectively. From the charge / discharge curve in FIG. 2B, in Comparative Example 2, the utilization rate was about 5% or less, and charge / discharge was impossible. On the other hand, from the charge / discharge curve in FIG. 2A, in Example 4, a capacity component derived from the Li insertion / deinsertion reaction into the high-temperature phase Li4WO5 was observed in the potential range of 0.2 V to 3.0 V (vs. Li / Li+), and it is understood that the battery functions as a solid-state battery.
[0136] The utilization rate of the negative electrode active material was 5% or less when a negative electrode active material with a Li / W ratio of 2 or less was used. From Experimental Example 1, this is considered to be due to (1) a side reaction occurring between the negative electrode active material and the garnet-type solid electrolyte during sintering, causing the negative electrode active material to be deactivated, and / or (2) the solid electrolyte decomposing, preventing the formation of an ion path in the electrode mixture. It was found that the use of a negative electrode active material with a Li / W ratio of more than 2 (e.g., 4 or more) makes it possible to charge and discharge a solid-state battery. In particular, it was found that a high reversible capacity can be obtained by making the crystal structure of the negative electrode active material have a high-temperature phase Li4WO5 structure.
[0137] [Table 2]
[0138] <Experimental Example 3> (Examples 13 to 19: Production of solid-state batteries) A solid-state battery was produced in the same manner as in Experimental Example 2, except that the negative electrode active material and solid electrolyte had the compositions shown in Table 3. The negative electrode active material was fired under the same conditions as in Example 4.
[0139] (Evaluation of solid-state batteries; utilization rate of negative electrode active material) In the same manner as in Experimental Example 2, the utilization rate of the negative electrode active material was calculated and evaluated.
[0140] It was found that, as long as the solid electrolyte has a garnet-type crystal structure, the solid-state battery can operate satisfactorily regardless of the composition of the solid electrolyte used. It was found that the inclusion of W in the garnet-type solid electrolyte is preferable because it results in a higher utilization rate.
[0141] [Table 3] [Industrial Applicability]
[0142] The solid-state battery of the present invention can be used in various fields where battery use or power storage is envisioned. By way of example only, a solid-state battery according to an embodiment of the present invention can be used in electronics packaging. The solid-state battery according to an embodiment of the present invention can also be used in the electrical, information, and communication fields where mobile devices and the like are used (e.g., electrical and electronic devices fields including small electronic devices such as mobile phones, smartphones, smart watches, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches, or mobile device fields), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like).
Claims
1. A solid-state battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the negative electrode layer includes a negative electrode active material and a garnet-type solid electrolyte, The negative electrode active material has the general formula (N): 【Chemistry 1】 (In formula (N), M is one or more elements selected from the group consisting of W (tungsten), Mo (molybdenum), Ta (tantalum) and Zr (zirconium), and includes W; M' is one or more elements selected from the group consisting of Na (sodium), K (potassium), Ca (calcium), Ti (titanium), V (vanadium), Sn (tin), Nb (niobium), Zn (zinc), Mn (manganese), Mg (magnesium), Al (aluminum), and Ga (gallium); α and β satisfy 2<α<10, 0<β<1.5, and 7≧α / β>2; γ satisfies 0≦γ<3; (ω satisfies 4<ω<9) The chemical composition is represented by The garnet-type solid electrolyte contains, in its chemical composition, Li (lithium), La (lanthanum), Zr (zirconium) and O (oxygen), The solid-state battery is a co-sintered solid-state battery.
2. The negative electrode active material is a low-temperature phase Li 4 WO 5 type crystal structure, high temperature phase Li 4 WO 5 Type crystal structure, and Li 6 WO 6 2. The solid-state battery according to claim 1, having one or more crystal structures selected from the group consisting of type crystal structures.
3. The negative electrode active material is a low-temperature phase Li 4 WO 5 Lithium type crystal structure or high temperature phase 4 WO 5 The solid-state battery according to claim 1 or 2, having a type crystal structure.
4. The solid-state battery according to any one of claims 1 to 3, wherein the garnet-type solid electrolyte further contains W (tungsten) in its chemical composition.
5. The garnet-type solid electrolyte has the general formula (G): 【Chemistry 2】 [In formula (G), A represents one or more elements capable of forming a solid solution in the Li site of the oxide having a garnet-type crystal structure; B I is one or more elements selected from the group consisting of elements that can take a trivalent valence and belong to Groups 1 to 3 and can take an eight-coordinated structure with oxygen; B II is one or more elements selected from the group consisting of elements that can take a valence other than trivalent among elements that belong to Groups 1 to 3 and can take an 8-coordination with oxygen; D I is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming a tetravalent valence among typical elements belonging to groups 12 to 15; D II is one or more elements selected from the group consisting of transition elements capable of forming 6-coordination with oxygen and elements capable of forming a valence other than 4 among typical elements belonging to Groups 12 to 15; α satisfies 3.0≦α≦8.0; β satisfies 2.5≦β≦3.5; γ satisfies 1.5≦γ≦2.5; ω satisfies 11≦ω≦13; x satisfies 0≦x≦1.0; y satisfies 0≦y≦1.0; z satisfies 0≦z≦2.
2. The solid-state battery according to any one of claims 1 to 4, having a chemical composition represented by the formula:
6. The negative electrode active material has a chemical composition represented by the general formula (N) and is a high-temperature phase Li 4 WO 5 The solid-state battery according to any one of claims 1 to 5, having a single-phase structure of a type crystal structure.
7. The negative electrode active material is such that, in the general formula (N), the α / β satisfies 3.8≦α / β≦6.5, and the M is W (tungsten), The solid-state battery according to claim 6 dependent on claim 5, wherein the garnet-type solid electrolyte satisfies the following condition (s1) in the general formula (G): Condition (s1): x=0, or A contains Ga and 0<x≦1.
0.
8. The negative electrode active material is such that, in the general formula (N), the α / β satisfies 3.8≦α / β≦6.5, and the M is W (tungsten), The solid-state battery according to claim 6 dependent on claim 5, wherein the garnet-type solid electrolyte satisfies the following conditions (s1) and (s2) in the general formula (G): Condition (s1): x = 0, or A contains Ga and 0 < x ≦ 1.0; Condition (s2): II includes Ta (tantalum) and W (tungsten).
9. The solid-state battery according to any one of claims 1 to 8, wherein the solid electrolyte layer contains a garnet-type solid electrolyte.
10. The solid-state battery according to any one of claims 1 to 9, wherein the positive electrode layer and the negative electrode layer are layers capable of absorbing and releasing lithium ions.
Citation Information
Patent Citations
Material for solid electrolyte
JP2014170734A
Negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2016201223A
Negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2017117775A
Negative electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2017135041A
Negative electrode active material, negative electrode, nonaqueous electrolyte power storage device, and method for manufacturing nonaqueous electrolyte power storage device
JP2018107130A